Idiopathic pulmonary fibrosis in a Christmas Island nuclear test veteran. (23rd November 2010) - Parfrey, H; Babar, J; Fiddler, CA; Chilvers, ER
Abstract : We describe the case of a 71-year-old man with idiopathic pulmonary fibrosis (usual interstitial pneumonia (UIP) pattern) diagnosed on clinical, radiological and lung function criteria, in accordance with the American Thoracic Society/European Respiratory Society consensus criteria (2000), who had been in close proximity to three atmospheric nuclear bomb blasts during military service in 1957. He does not have clubbing and clinically and radiologically his lung disease is stable. He also has bladder carcinoma and carotid arteriosclerosis, both recognised consequences of radiation injury. This is the first reported case of UIP in a nuclear test veteran. Awareness of this potential association is important given the current attempts of the British Nuclear Test Veterans Association to gain compensation for claimed injuries.